Chloroplast Biotechnology Methods and Protocols - Maliga, Pal (Methods in Molecular Biology, Methods and Protocols, 2014)
In Chloroplast Biotechnology: Methods and Protocols, expert researchers in the field detail many of the methods which are now commonly used in chloroplast molecular biology.  Chapters focus on essential background information, applications in tobacco, and protocols for plastid transformation in crops, and Chlamydomonas and Bryophytes. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoidance of known pitfalls.   Authoritative and practical,  Chloroplast Biotechnology: Methods and Protocols seeks to aid scientists who study chloroplast molecular biology as well as those interested in applications in agriculture, industrial biotechnology, and healthcare